WORKSHOP EVALUASI PEMBELAJARAN JARAK JAUH BERBASIS GAME - Rani Kurnia Putri; Silviana Maya Purwasih; Restu Ria Wantika; Prayogo Prayogo (STKIP PGRI Sidoarjo, 2021)
Schools that carry out distance learning, or better known as online, should be more able and accustomed to following the development of Multimedia technology. However, it turns out that this does not necessarily apply to all schools that carry out learning through online media. From the results of direct interviews with teachers and headmaster at SMKN 1 Jetis Mojokerto, it was found that teachers still had difficulties in using multimedia for the learning process, and students also felt uninterested in participating in online learning activities, so that the tasks given by teachers are also ignored by students. This is very troubling considering that online learning is a must in this pandemic era. Based on these problems, Based on these problems, PPM Lecturers of the Mathematics Education Study Program need to carry out PPM activities with the theme is